The Buddha in Lanna : art, lineage, power, and place in northern Thailand - Chiu, Angela S. (University of Hawaiʻi Press, 2017)
This work is an in-depth historical study of the Thai tradition of donation of that most iconic of Thai art objects, the Buddha image. Angela S. Chiu introduces stories from tamnan (chronicles), monastic histories and legends from the Lanna region centred in today's northern Thailand.